1998
DOI: 10.1176/ajp.155.11.1600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antipsychotic Treatment on Polysomnographic Measures in Schizophrenia: A Replication and Extension

Abstract: These data demonstrate partial improvement of some but not all EEG sleep measures in schizophrenic patients through the course of neuroleptic treatment. They suggest that shortened REM latency and disturbed sleep continuity might represent reversible state abnormalities, while reduced slow-wave sleep may represent a more persistent trait abnormality in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…In contrast with the wellknown role of other neurotransmitter systems in sleep physiology, the consequences of specific dopamine manipulations are far from being clearly understood (Pace-Schott and Hobson 2002). However, the results obtained fall in the line with the global improvement in sleep continuity generally described after antipsychotic administration in schizophrenic patients (Stephan et al 1991;Maixner et al 1998). Specifically, patients under haloperidol treatment usually show increases in TST and sleep efficiency but no change, or even a decrease, in the amount of SWS (Itil et al 1970).…”
Section: Discussionsupporting
confidence: 71%
“…In contrast with the wellknown role of other neurotransmitter systems in sleep physiology, the consequences of specific dopamine manipulations are far from being clearly understood (Pace-Schott and Hobson 2002). However, the results obtained fall in the line with the global improvement in sleep continuity generally described after antipsychotic administration in schizophrenic patients (Stephan et al 1991;Maixner et al 1998). Specifically, patients under haloperidol treatment usually show increases in TST and sleep efficiency but no change, or even a decrease, in the amount of SWS (Itil et al 1970).…”
Section: Discussionsupporting
confidence: 71%
“…Considering known cholinergic effects on REM latency and other sleep measures Gillin and Sitaram 1984), these data are consistent with the hypothesis of increased cholinergic activity in schizophrenia and its implication in the production of negative symptoms. In related studies (Taylor et al 1991;Maixner et al 1998;Tandon 1997), we observed that polysomnographic measures partially normalized following antipsychotic treatment (with neuroleptics, clozapine, and risperidone). Assuming that increased cholinergic activity partly underlies polysomnographic abnormalities in schizophrenia at drug-free baseline, these data may indicate a trend for increased cholinergic activity to partially normalize with neuroleptic therapy (Figure 1) (Tandon and Greden 1989;Tandon et al 1990a).…”
Section: In Vivo Measurement Of Central Cholinergic Activitymentioning
confidence: 69%
“…As a general rule, first-generation APs improve sleep maintenance, increasing TST and SE and reducing SL and waking after sleep onset, although their effects on REML, REM time, and REM EM density differ [56][57][58][59][60][61]. Chlorpromazine increases SWS time, an effect consistent with a related increase in REML [56].…”
Section: Antipsychotics: Effects On Sleep Patternsmentioning
confidence: 87%